Allele‐Dose Association of the C5orf30 rs26232 Variant With Joint Damage in Rheumatoid Arthritis. Issue 10 (24th September 2013) - Teare, M. Dawn; Knevel, Rachel; Morgan, Michael D.; Kleszcz, Agnieszka; Emery, Paul; Moore, David J.; Conaghan, Philip; Huizinga, Tom W. J.; Morgan, Ann W.; van der Helm‐van Mil, Annette H. M.; Wilson, Anthony G.
<x xml:space="preserve">Abstract</x> Objective There is increasing evidence to indicate that genetic factors contribute significantly to radiologic joint damage in rheumatoid arthritis (RA). The aim of the present study was to determine whether genotypes of 10 recently identified RA susceptibility loci are associated with radiologic severity. Methods A 2‐stage study was performed using 3 Northern European RA populations: a British cross‐sectional population (discovery cohort; n = 885) and the Leiden Early Arthritis Clinic (EAC) cohort (n = 581) and Yorkshire Early Arthritis Register (YEAR) cohort (n = 418) (validation cohorts). Radiologic damage was assessed using a modified Larsen method for scoring radiographs (in the discovery cohort) or modified Sharp/van der Heijde score (in the 2 validation cohorts). A meta‐analysis was performed to bring together the evidence from the 3 studies, using data on radiologic severity of joint damage from a single time point. Results An allele‐dose association of rs26232 was present in the discovery population (P = 4 × 10−4); the median modified Larsen scores of radiologic joint damage per genotype were 31 (for those with CC), 27 (for those with CT), and 16 (for those with TT). The allele‐dose association of rs26232 was replicated in both the Leiden EAC cohort during the initial 7 years of RA (P = 0.04) and the YEAR cohort (P = 0.039). In a fixed‐effects meta‐analysis of all 3 studies, the per T allele effect on the ratio of radiologic severity scores was 0.90 (95% confidence interval 0.84, 0.96; P = 0.004). Conclusion The variant rs26232, in the first intron of the C5orf30 locus, is associated with the severity of radiologic damage in RA and is independent of established prognostic biomarkers. The biologic activities of C5orf30 are unknown, but our genetic data suggest that it is involved in mediating joint damage in RA.